"Nothing about us, without us": Conducting participatory action research among and with persons with disabilities in humanitarian settings. Issue 3 (September 2018) - Tanabe, Mihoko; Pearce, Emma; Krause, Sandra K
Standard approaches to data collection can present challenges to persons with disabilities participating in research processes. The Women's Refugee Commission applied a participatory model to examine the intersections of sexual and reproductive health and disability in Kenya, Nepal, and Uganda. Respecting the Convention on the Rights of Persons with Disabilities and a rights-based framework to research, the study engaged a variety of stakeholders—including organizations of persons with disabilities—from its inception and design, through to implementation and recommendation formulation. In Nepal especially, persons with disabilities played a central role in gathering the information from refugee women, men, and adolescents with physical, intellectual, sensory, and psychosocial impairments. Reasonable accommodations for the data collectors included the provision of personal assistants, vehicles for movement, sign language interpretation, Braille documents, and tactile ink-based diagrams; use of a "talking pen;" and creation of a "supporter" role in the facilitation process. Daily debriefings provided opportunities for collective improvement and reflection. The study offers considerations for other researchers to extend their research—on the part of the study participants and in the research process itself—to operationalize a rights-based, inclusive, and empowering approach to qualitative research.